2015
DOI: 10.5588/pha.15.0004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intensified case-finding strategies on childhood TB case registration in Nepal

Abstract: A package of intensified case-finding strategies in children was associated with an increase in childhood TB case registrations in Nepal. Additional diagnostic approaches to increase case registrations also need to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…Studies from Pakistan, India, Nepal and Nigeria have shown that intensified case finding can result in large increases in childhood TB case notification [9,[13][14][15]. Our study indicates that injection of new resources through focused active TB case finding and contact tracing efforts can substantially raise the baseline TB case notification among children.…”
Section: Discussionmentioning
confidence: 61%
“…Studies from Pakistan, India, Nepal and Nigeria have shown that intensified case finding can result in large increases in childhood TB case notification [9,[13][14][15]. Our study indicates that injection of new resources through focused active TB case finding and contact tracing efforts can substantially raise the baseline TB case notification among children.…”
Section: Discussionmentioning
confidence: 61%
“…Hence, ACF affords a high yield HIV testing platform to help achieve the universal target of diagnosing 90% of all people living with HIV. [18] Unfortunately, limited data is available to inform ACF in children living in TB/HIV-high burden settings [9, 12, 14]. Implemented in a setting with extremely high TB and HIV infection rates, our pediatric-focused contact tracing program demonstrated that the yield of contact tracing is 1.43 fold greater in HIV-affected households.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous peer-reviewed articles documenting that household proximity to a bacteriologically confirmed adult TB is an important predictor of a positive TB screen in children, there is very little published data on ACF interventions targeting childhood TB in TB high-burden, resource-limited settings [12, 13]. Gaps in the literature regarding the childhood TB diagnostic cascade include limited evidence to inform standardized childhood TB contact tracing algorithms or to improve the diagnosis of paucibacillary TB in children [14]. As there is little evidence available regarding the yield of household contact and source case investigations among children in TB/HIV high burden settings, the objective of our study was to evaluate the yield and additionality of these strategies in a TB/HIV high burden setting while prioritizing the identification of TB among child contacts.…”
Section: Introductionmentioning
confidence: 99%
“…16 The impact of the ICF activities in several districts on improving childhood TB CNR was documented recently in Nepal. 17 However, ZAMSTAR, a community-randomised trial in Zambia and the Western Cape province of South Africa, showed that neither community-level enhanced TB case finding nor household level TB-HIV care led to a statistically significant reduction in the TB burden in the community. It is important to note that the trial involved only enhanced case finding, and not systematic screening (active screening), as was done in the present study.…”
Section: Public Health Actionmentioning
confidence: 99%